The critical requirements for the principalship from an analysis of critical incidents as reported by public elementary school teachers in Manila - Malicdem, Godofredo S. 1907- ([Quezon City University of the Philippines], 1957)
This study determines the critical requirements for principalship. It investigated the effective and ineffective acts related to the principalship and its implications on the principalship preparation progam and in-service training.
Bibliography: l. 138-144.
Mimeographed
Thesis (M.Ed.)--University of the Philippines, 1957
Vita
Keywords: School superintendents and principals